Social Media Marketing Strategy to Improve Customer Satisfaction and Repurchase Intention Through Brand Equity in E-Commerce - Abnar Uhibah Ulhaq; Ika Baskara; Fajar Satria; Primasatria Edastam (International Publisher (YAPENBI), 2025)
This study aims to analyze the influence of social media marketing strategies in increasing customer satisfaction and repurchase intentions through brand equity on e-commerce platforms in Indonesia. This study uses a quantitative approach with the Structural Equation Modeling Partial Least Square (SEM-PLS) method . A total of 150 respondents who are active e-commerce users in the Jabodetabek area became the research sample. The results of the study indicate that social media marketing activities have a significant positive effect on brand equity , which is mediated by brand love and brand trust . In addition, brand equity has a direct relationship with customer satisfaction , which then affects repurchase intention . This study also reveals that interactive, responsive, and relevant social media marketing strategies contribute to increasing emotional connections between consumers and brands, which are important factors in building long-term loyalty. Positive experiences felt by consumers through interactions on social media not only improve their perceptions of the brand but also create deep trust relationships. The practical implications of this study indicate that business actors need to pay attention to the elements of transparency, consistency, and personalization in every marketing activity they do on social media. With this approach, businesses can create added value to brand equity while increasing customer retention. This study also emphasizes the importance of utilizing technology such as artificial intelligence to support more effective real-time interactions with consumers. This strategy is believed to not only be able to improve brand image, but also motivate consumers to make consistent repeat purchases. Therefore, this study provides a significant contribution, both in the academic context and managerial practice, especially in helping e-commerce businesses in Indonesia to develop more innovative and sustainable social media-based marketing strategies.